Reconstruction of KH. Abdul Ghofur's Jurisprudential Reasoning from the Perspective of Maqāṣid al-Syarī'ah: A Study of Economic Development at Pondok Pesantren Sunan Drajat - R. Zainul Mushthofa; Siti Aminah (GHAITSA : Islamic Education Journal, 2026)
This study conducts an epistemological analysis of the jurisprudential reasoning (fiqh) of KH. Abdul Ghofur, a charismatic Islamic scholar from Lamongan widely recognized as a reformist figure in contemporary Islamic thought. His notable contribution lies in the effort to integrate social, humanitarian, and economic values into a dynamic and solution-oriented framework of Islamic law. Employing the maqāṣid al-syarī'ah approach, this research focuses on re-examining the intellectual framework of KH. Abdul Ghofur in the context of reconstructing Islamic law to be more contextual, adaptive, and responsive to the challenges of modernity and the social changes confronting Muslim societies. This qualitative study employs a library research method, examining KH. Abdul Ghofur's writings, speeches, and social practices in conjunction with classical and modern Islamic legal theories. A descriptive-analytical approach is applied to uncover the structure of his jurisprudential thinking, which emphasizes the balance between normative texts and social contexts. The findings reveal that KH. Abdul Ghofur's jurisprudential reasoning does not solely rely on formal legalistic interpretations of texts but is firmly rooted in the ethics of public welfare (maṣlaḥah 'āmmah) as the core of maqāṣid al-syarī'ah. Consequently, his thought can be categorized as a model of social jurisprudence (fiqh ijtimā'ī) that prioritizes substantive justice and advocates for the welfare of the Muslim community. This thinking demonstrates significant relevance to efforts at re-actualizing Islamic law to address the socio-economic challenges facing the community in a transformative and sustainable manner.